2011
DOI: 10.1187/cbe.11-07-0061
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Not Associated with Student Learning in a Random Sample of College Biology Courses

Abstract: Previous research has suggested that adding active learning to traditional college science lectures substantially improves student learning. However, this research predominantly studied courses taught by science education researchers, who are likely to have exceptional teaching expertise. The present study investigated introductory biology courses randomly selected from a list of prominent colleges and universities to include instructors representing a broader population. We examined the relationship between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
248
3
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(280 citation statements)
references
References 49 publications
(87 reference statements)
4
248
3
17
Order By: Relevance
“…The success of active learning is associated with effective pedagogical approaches to curricular design (Andrews et al 2011). We took a constructivist approach to active learning, accepting that students must integrate new information with their existing knowledge frameworks (Chi 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The success of active learning is associated with effective pedagogical approaches to curricular design (Andrews et al 2011). We took a constructivist approach to active learning, accepting that students must integrate new information with their existing knowledge frameworks (Chi 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They have also reported 53% of students felt the course is more appealing when they heard about flipping approach. These disappointing results could be attributed to the breadth of the student population or the instructors' inexperience (Andrews, Leonard, Colagrove, & Kalinowski, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…"Active learning done badly is worse than a good lecture," says Leips. A 2011 survey of biology teachers at 77 US universities found that, even though most of them claimed to be using at least some active-learning methods, few of them were doing it properly 6 .…”
Section: Culture Shockmentioning
confidence: 99%